Ultrasonic-promoted defect activation and structural rejuvenation in a La-based metallic glass. (February 2023) - Yuan, C.C.; Lv, Z.W.; Li, X.; Pang, C.M.; Liu, R.; Yang, C.; Ma, J.; Zhu, W.W.; Huang, B.; Ke, H.B.
Abstract: Ultrasonic-assistant rejuvenation in a La-based metallic glass was demonstrated by means of nanoindentation for the first time. A more pronounced nanoindentation creep behavior along with mechanical softening was detected. It is proposed to be associated with the activation of flow defects with long characteristic relaxation time at a low loading rate and short characteristic relaxation time at a high loading rate during anelastic deformation process based on the Maxwell-Voigt model. Such rejuvenation behavior also leads to an unstable plastic flow and a relatively low energy barrier for atomic diffusion during the fast growth process of crystalline phases accompanied with the reduced glass transition and crystallization temperatures. Our studies might provide insights into the microscopic deformation mechanism of glassy materials, which could help in seeking the novel applications of amorphous alloys such as ultrasonic-assistant cold joining or molding. Highlights: The ultrasonic-assistant rejuvenation in a La-based metallic glass was investigated by means of nanoindentation. A high-energy state with the reduced activation energy for crystalline growth was achieved under ultrasonic vibration. The mechanical softening in the ultrasonic-treated metallic glass can be interpreted by the defect-activation mechanism.